Produksi Serasah Mangrove di Pesisir Tangerang, Banten - Gilang Rusrita Aida; Yusli Wardiatno; Achmad Fahrudin; Mohammad Mukhlis Kamal (Jurnal Ilmu Pertanian Indonesia, 2014)
Mangrove ecosystem plays an important role in contributing the organic matter from litter produced which is amajor link of the food web in mangrove ecosystem. The research was conducted to estimate litterfall production ofmangroves in Tangerang coastal area. The structure and composition of the mangrove ecosystem consists ofAvicenia marina, Avicenia alba, Rhizophora mucronata, and Sonneratia caseolaris with density and diameter ofmangrove trees about 3 23 tress/100 m2 and 4.8 38.2 cm, respectively. The results of station groupings based onthe structure and composition of mangrove with environmental parameters showed the highest production oflitterfall generated by group II (station 4; consists of Avicenia marina and Rhizophora mucronata), followed bygroup III (station 6; consists of Sonneratia caseolaris) and group I (station 1, 2, 3, and 5; of Avicenia alba, Aviceniamarina, and Rhizophora mucronata). Litterfal production of group II reached 3.86 ± 0.22 g/m2/day, followed by groupIII and group I (3.63 ± 2.2 g/m2/day and 2.88 ± 0.99 g/m2/day, respectively). Overall, the total production of litterfallper day in the coastal area reached 3.45 g/m2/day with leaf as the main component (>80%), followed by twigs andreproductive organs.